Politeness Maxim In the film ” Laskar Pelangi” - Budiati Budiati (UIN Salatiga, 2012)
Sentential implicature is something meant or implied that is proposed to avoid impoliteness in making harmonious conversation. For the sake of politeness it was postulated cooperative politeness and maxims; tact maxim, approbation maxim, generosity maxim, modesty maxim, agreement maxim and sympathy maxim. The measurement of politeness or impoliteness is also determined by the four factors; power, range, distance and familiarity. In “Laskar Pelangi” the movie, it was found some maxims with Indonesian cultural background for its politeness. Politeness was shown by addressing someone just by name or by saying “Mr.” and “Mrs”, according to the power and relationship, minimizing dispraise of others, and mentioning something or someone indirectly.